An Atypical Presentation of Kawasaki Disease and Potential Markers for Diagnosis - Tzu Ning Liu BS; Abigail C. Kuplicki BS, BA; Jocelyn Y. Ang MD (SAGE Publishing, 2023)
Cervical lymphadenopathy is seldom the initial symptom of Kawasaki disease (KD), making diagnosis difficult in early node-first Kawasaki disease (NFKD). Early treatment is important to prevent cardiovascular sequelae. This report discusses a case of a 4-year-old African American female with NFKD and retropharyngeal phlegmon who was initially treated with antibiotics for cervical lymphadenitis. She later developed classic symptoms of KD, including mucositis, conjunctivitis, palmar erythema, and truncal rash. KD was then suspected and treated appropriately, with the patient experiencing rapid clinical improvement. Early misdiagnosis of NFKD is not uncommon, but certain indices, such as patient age, elevated absolute neutrophil count, or elevated liver enzymes, may be helpful in increasing clinical suspicion. NFKD and retropharyngeal phlegmon remain a rare presentation of an already known condition. The case presented here emphasizes the need for KD to be a differential diagnosis in cases of cervical lymphadenitis and retropharyngeal abscess refractory to antibiotic treatment.